Kauno suaugusiųjų institutas - Bubnys, Gediminas; Kriaučeliūnas, Zenonas Simas (Lietuvos istorijos studijos, 2003)
Vocational training was the main goal of German professional unions. The attitude was led by two circumstances: firstly, the lack of workers of technical professions; secondly, the wish to hold the training of new technical professions in their hands. Vocational training was organized not only in part-time courses but in Adult Institutes as well. These were vocational schools, which were supported by the central bureau of professional unions. Kaunas Adult Institute was one of them, which was founded on the 18th of August 1941 and run by the headmaster K. Račinskis since the 16th of August 1944. Head assessor of education Dr. Pr. Germantas-Meškauskas confirmed the statute of the institute. Later, the Adult Institute was founded in Vilnius. The increased number of institutes inspired the necessity of a new statute. "The Temporal Statute of Adult Institute" was confirmed on the 1st of January 1942. Since 4 February 1942, Kaunas Adult Institute has been named as "the Central Adult Institute," and the next year adult institutes were founded in Panevėžys and Šiauliai. The Central Adult Institute didn’t last long, because the course of some specialties survived for a few years only. 336 students graduated from the institutes during the first school year. In 1944, March and April, there were 583 students in the Central Adult Institute. The work of the central and local adult institutes was interrupted in the summer of 1944 because of the second Soviet occupation. The work of this institution shows that even during the occupation years in Lithuania, education and professional training were not interrupted.